Catalytic steam gasification of lignite for hydrogen-rich gas production in a decoupled triple bed reaction system. (1st February 2017) - Xiao, Yahui; Xu, Shaoping; Tursun, Yalkunjan; Wang, Chao; Wang, Guangyong
Graphical abstract: Highlights: The configuration of decoupled triple bed system has an advantage on tar destruction. Ni/olivine as bed material is effective for tar destruction and hydrogen production. Olivine and NiO/olivine as both catalysts and oxygen carriers affect lignite gasification. Abstract: Catalytic steam gasification of an Inner Mongolia lignite for hydrogen-rich gas production was investigated in a decoupled triple bed reaction system with olivine and Ni/olivine as both solid heat carrier and in-situ tar cracking/reforming catalyst. In the system, tar cracking/reforming, pyrolysis/gasification, and char combustion reactions are decoupled into three separated reactors, i.e. a reformer, a fuel reactor and a combustor, which are connected in series by solid heat carrier. The system configuration provides an option to strengthen tar cracking/reforming reaction to improve hydrogen-rich gas production and tar removal. Specifically, using olivine and Ni/olivine in a mass ratio of 1:1 as circulating bed material and in-situ tar cracking/reforming catalyst, a product gas with the H2 concentration of 51.7 vol.% and the tar content of 2.2 g/Nm 3 has been obtained at the pyrolyzer temperature of 700 °C, reformer temperature 850 °C, steam to carbon mass ratio (S/C) 1.2, and ratio of bed material circulating rate to coal feeding rate (C/F) 8.0. Nevertheless, the gasification performance suffered from the limited char steam gasification.